Analyses of hierarchical structures in vulcanized SBR rubber by using contrast‐variation USANS and SANS. Issue 3 (31st May 2021) - Takenaka, Mikihito; Nishitsuji, Shotaro; Watanabe, Yuki; Yamaguchi, Daisuke; Koizumi, Satoshi
Abstract : Contrast‐variation (ultra)‐small‐angle neutron scattering [(U)SANS] of vulcanized poly(styrene‐ran‐butadiene) (SBR) rubber has clarified that ZnO clusters surrounded by dense networks of SBR exist in the rubber. The size of the ZnO clusters is of the order of 1000 Å. Abstract : The hierarchical structures of poly(styrene‐ran‐butadiene) (SBR) rubber vulcanized with sulfur in a swollen state were investigated by using the contrast‐variation ultra‐small‐angle neutron scattering (USANS) and small‐angle neutron scattering (SANS) techniques. The following three levels of hierarchical structure were found: (i) ZnO clusters surrounded by dense SBR networks of the order of 1000 Å in size, (ii) dense networks of SBR in the size range of 70–100 Å and (iii) a mesh size of the network of the order of 10 Å. In addition to the three kinds of structure, dense networks without ZnO of the order of 1000 Å were also observed. These last networks were formed by ZnO's reaction with sulfur. However, the ZnO clusters disappeared, which is associated with the diffusion of Zn.